Organization of Poor Minors Labor by Charity Societies in the Mid-Nineteenth Century. A Poznan Case - Łysakowska-Trzoss, Agata Karolina (Studia Historiae Oeconomicae, 2024)
One of the means of help offered by the 19th century charity societies was finding employment for the poorest. Among their beneficiaries were also children, whose work was a substantial contribution to the finances of their families. The age limit in this case was 14 – above that age children from the poor families were sent to work (girls most often to service, and boys – to apprenticeship). Attempts were made to send them to recommended houses or craftsmen. One of the organizations which helped children to find employment was the Polish Ladies Charity Society in Poznan founded in 1845, whose activists conducted detailed interviews of families requesting help. The goal of the text is to analyze the situation of the poor minors who worked in Poznan. The source base for the following research were two Card Indexes: the alphabetic Card Index of proteges of the Polish Ladies Charity Society with Celestyna Działyńska’s hand notes regarding grants, and the Card Index of proteges of the TDDP, which was organized by districts and led by women reporting to Działyńska, auxiliary reports and private notes of the founder of the Society, Celestyna działyńska, were included. In the following qualitative and quantitative methods were used, combined with the case study approach. The members of the Poznań Charitable Societies, which functioned in the Middle of 19th century, not only organized workplaces for the minor, but also took care of their education and wellbeing. They paid special attention to the role of a child in their family and checked the circumstances when a child, if of an appropriate age for employment, didn’t go to work. In the large families, when the oldest children established their own households, the younger children could still work and contribute to the family’s finances.